The role of migratory birds in the spread of coronaviruses - Piryaei, Mohammad Reza; Tabari, Teimur; Peighambari, Seyed Mostafa; Vasfi Marandi , Mehdi; Ghahremani , Nima (Journal of Poultry Sciences and Avian Diseases, 2024)
Since the discovery of viruses, humans have always faced a great challenge in dealing with their subsequent diseases. Coronaviruses have created huge challenges in the world. Coronaviruses are RNA genome viruses from the Coronaviridae family that can cause different diseases in both poultry and humans, but no evidence has been provided for their zoonotic potential, which may be due to the different genera of the viruses that cause diseases in these hosts. There are different ways of transmission for the coronaviruses with airborne being the most common and important route. However, the role of migratory birds in their spread has been noticed recently. Due to the novelty and importance of this issue, we decided to conduct an analytic study on the role of migratory birds in the spread of coronaviruses. The results show that due to the high possibility of the virus mutations in the host's body, the interspecies barrier can be broken and we can see the direct transmission of the coronaviruses from birds to humans. However, due to the novelty of this topic, more studies are required to acquire a comprehensive knowledge on this matter.